The Utilization of E-Poster in Teaching and Learning - Azureen, Abd Aziz; Phawani, Vijayaratnam; Menaga, Vesudevan (The Association of Professional Researchers and Academicians (The APRA), United Kingdom, 2022)
Posters thrive in education libraries or classrooms as attractive items, yet few realize the educational potential of the poster. Posters are colourful eye-catching learning media that could boost the learning atmosphere. E-Poster sessions have become common as a presentation mode for virtual conferences as well as face-to-face learning. These poster sessions comprise numerous forms of information captured in digital formats such as videos, interactive lectures, slideshows, photo albums, short games, and other elements. E-Posters could be archived to the Web, to digital sources or libraries, or to more closed collections. This paper aims to further advance the value of the e-poster as a new useful teaching instrument in the educational setting.